2010
DOI: 10.1007/s00455-009-9271-7
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of Anterior Cervical Plate into Pharynx with Pharyngotracheal Fistula

Abstract: We report a 58-year-old woman who presented with dysphagia and recurrent episodes of coughing and choking during swallowing 10 years after anterior cervical discectomy and fusion with implantation of an anterior cervical plate. Barium esophagography revealed erosion of the cervical plate through the posterior wall of the pharyngoesophageal junction with an extraluminal collection that extended inferiorly as a track through the posterior wall of the trachea, producing a pharyngotracheal fistula. The pharyngeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Chronic contact between the pharyngoesophageal junction and adjacent cervical plate may cause pressure necrosis and a foreign body reaction with subsequent erosion of the plate into the lumen. 6 In this case, the esophageal stent likely increased the pressure between the cervical plate and the mucosal wall, resulting in pressure necrosis and a foreign-body reaction that eroded the intervening tissue between the esophageal lumen and the cervical plate. Our major concern was the prospect of the patient's developing osteomyelitis and colonization of the disc-bone interface.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chronic contact between the pharyngoesophageal junction and adjacent cervical plate may cause pressure necrosis and a foreign body reaction with subsequent erosion of the plate into the lumen. 6 In this case, the esophageal stent likely increased the pressure between the cervical plate and the mucosal wall, resulting in pressure necrosis and a foreign-body reaction that eroded the intervening tissue between the esophageal lumen and the cervical plate. Our major concern was the prospect of the patient's developing osteomyelitis and colonization of the disc-bone interface.…”
Section: Discussionmentioning
confidence: 97%
“…A much less common but serious complication is erosion or migration of a cervical plate into the lumen of the pharynx or esophagus. [6][7][8][9] The mechanism for erosion of an anterior cervical plate is not well-understood. The relatively sharp edge of a screw or plate abutting the pharynx or esophagus has been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…[67] In the trauma setting, vertebral body fracture may require corpectomy in which ACDF is typically performed in conjunction with posterior instrumentation. [26]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, chronic compression of the esophagus against the anterior cervical plate during swallowing can result in pressure necrosis and eventually perforation and fistula formation. [2457]…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such implant-associated complications include screw loosening, screw breakage, and plate breakage, screw pullout with or without migration into gastrointestinal tract (8, 13,16,24,27,37). Rarely, erosion of anterior cervical plate into pharynx with pharyngotracheal fistula (22) or pharyngocutaneous fistula may occur (31). Although rigid plate design with screws rigidly locked to the plate is thought to provide a better fixation for the treated spinal segment than a dynamic design in which the screws may slide when the graft is settling (37), Pitzen et al (28) recently found that dynamic cervical plate designs provide less implant complications, less implant failure-related revision surgery and faster speed of fusion compared with rigid cervical plates.…”
Section: A B Azab W Et Al: Anterior Cervical Diskectomy With Zero-prmentioning
confidence: 99%